Comparison of the oral health-related quality of life and dental pain in symptomatic irreversible pulpitis and pericoronitis - MUMCU, GONCA; ŞİŞMAN KİTAPÇI, NUR; KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (ELSEVIER TAIWAN, 2012)
Background/purpose: The oral health-related quality of life (OHRQoL) reveals important information about a patient's perceptions in clinical practice, and pain is a critical point when evaluating OHRQoL in clinical practice. The aim of the study was to compare pain patterns by means of the Dental Pain-Screening Questionnaire (DePaQ) and an OHRQoL evaluation between symptomatic irreversible pulpitis and pericoronitis. Materials and methods: In this cross-sectional study, 50 patients with symptomatic irreversible pulpitis (with a female:male ratio of 22:28 and a mean age of 35.6 +/- 11.8 years) and 38 patients with pericoronitis (with a female:male ratio of 21:17 and a mean age of 26.3 +/- 9.08 years) were selected. In addition to a visual analogue scale (VAS, 0-100 mm), dental pain was evaluated by means of a Dental Pain Questionnaire (DePaQ). The Oral Health Impact Profile-14 (OHIP-14) was used to examine the OHRQoL status. Results: Scores of the OHIP-14 and VAS were significantly higher in patients with irreversible pulpitis (29.9 +/- 11.8 and 91.80 +/- 10.03, respectively) compared to those suffering from pericoronitis (18.6 +/- 8.7 and 51.05 +/- 36.67, respectively; P < 0.001). According to the DePaQ, the presence of continuous pain, pain radiating to the surrounding area, pain when chewing or eating on the side of the mouth with the affected teeth, pain experienced as an electric shock, and difficulty sleeping were related to a poor OHIP-14 score in symptomatic irreversible pulpitis (33.5 +/- 10.57, 30.82 +/- 11.4, 30.30 +/- 11.55, 33.92 +/- 10.28, and 27.53 +/- 11.77, respectively) compared with those with pericoronitis (20.09 +/- 11.27, 20.37 +/- 7.85, 19.64 +/- 7.87, 20.56 +/- 9.69, and 19.88 +/- 7.9, respectively; P = 0.003, <0.001, <0.001, <0.001, and 0.005, respectively). VAS scores significantly differed between groups according to all DePaQ items (P < 0.05). Conclusion: The DePaQ gives detailed information about clinical conditions related to pain and the OHRQoL status in both symptomatic irreversible pulpitis and pericoronitis. VAS scores differed between the groups according to the DePaQ items. Copyright (c) 2012, Association for Dental Sciences of the Republic of China. Published by Elsevier Taiwan LLC. All rights reserved.
Keywords: dental pain; pericoronitis; quality of life; symptomatic irreversible pulpitis; VAS; 3RD MOLAR SURGERY; FLARE-UP; IMPACT; PREVALENCE; VALIDATION; RECOVERY; VISIT